Asymptomatic Giant Left Atrium - Funk, Michael (Clin Cardiol, 2010)
Giant left atria (GLA) is a condition where the left atrial diameter exceeds 65 mm.(1) It is closely related to rheumatic mitral valve regurgitation or mixed mitral disease with predominant regurgitation and tends not to occur in patients with mitral regurgitation due to other causes.(2) The majority of patients are symptomatic with the most common symptoms being that of shortness of breath, dysphagia, palpitations, chest pain, and thromboembolic events.(3) Massive asymptomatic enlargement of the left atrium is a rare entity. We present such a case. Copyright © 2010 Wiley Periodicals, Inc.